2012
DOI: 10.1089/gtmb.2012.0004
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-6-572G/C Gene Polymorphism and the Risk of Intracranial Aneurysms in a Chinese Population

Abstract: Interleukin-6 (IL-6) is an important proinflammatory cytokine that plays an important role in the pathogenesis of intracranial aneurysms (IAs). The aim of this study was to investigate the association between the IL-6-572G/C polymorphism and the risk of IAs in a Chinese population. The IL-6-572G/C gene polymorphisms in 220 IA cases and 220 controls were analyzed using the polymerase chain reaction-restriction fragment length polymorphism method. The IL-6-572GG (odds ratio [OR]=3.35, 95% confidence intervals [C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…21 The evidence base was, however, small compared with other complex disorders. 21 The interleukin (IL)-6-572GG genotype has been shown to be associated with a heightened risk of IA in a Chinese population, 26 and this finding is consistent with other published reports in Chinese Han and Cantonese populations. 27,28 A region between introns 7 and 15 of the cyclindependent kinase inhibitor 2B antisense RNA-1 (CDKN2BAS) gene, carrying the rs1333040-T allele, has also been associated with an increased risk of IA in Japanese patients.…”
Section: Discussionsupporting
confidence: 87%
“…21 The evidence base was, however, small compared with other complex disorders. 21 The interleukin (IL)-6-572GG genotype has been shown to be associated with a heightened risk of IA in a Chinese population, 26 and this finding is consistent with other published reports in Chinese Han and Cantonese populations. 27,28 A region between introns 7 and 15 of the cyclindependent kinase inhibitor 2B antisense RNA-1 (CDKN2BAS) gene, carrying the rs1333040-T allele, has also been associated with an increased risk of IA in Japanese patients.…”
Section: Discussionsupporting
confidence: 87%
“…Morgan et al (2006) first reported that IL6 promoter polymorphism rs1800796 (−572C/G) and rs1800795 (−174G/C) are associated with IA in Caucasian population and 572C/174C haplotype having a greater risk [ 10 ]. Subsequent studies with these variants in Italian and Chinese population had shown conflicting results [ 11 14 ]. While rs1800796 and rs1800795 were not associated with IA in Italian population [ 11 ], it was a conflict of allelic associations in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…While rs1800796 and rs1800795 were not associated with IA in Italian population [ 11 ], it was a conflict of allelic associations in Chinese population. In Han Chinese [ 12 ] and west Chinese population [ 14 ], G allele proved to be a risk allele, whereas in Cantonese population, C allele turned out to be a risk allele for IA [ 13 ]. None of these allelic associations for IL6 could be replicated in our study population for IA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, 3 articles investigated the associations between TNF-α rs1800629 polymorphism and risk of IA; 13,14,17 11 articles investigated the associations between IL gene (IL-1α, IL-1β, IL6, and IL-12B) polymorphisms and risk of IA. 11,12,[17][18][19][20][21][22][23][24][25] Detailed characteristics of the included studies are summarized in Table 2. A detailed flow chart of study selection is presented in Fig.…”
Section: Characteristics Of the Available Studiesmentioning
confidence: 99%